2007
DOI: 10.1002/jca.20135
|View full text |Cite
|
Sign up to set email alerts
|

Dextran‐sulfate‐adsorption of atherosclerotic lipoproteins from whole blood or separated plasma for lipid‐apheresis—Comparison of performance characteristics with DALI and lipidfiltration

Abstract: For many years dextran sulfate adsorption (DSA) treatment of separated plasma has been an established technology for low-density lipoprotein (LDL)-elimination. Recently a system for the treatment of whole blood based on DSA was introduced into clinical practice. To further characterize DSA treatment of whole blood, the performance characteristics of both DSA modalities were compared at two investigational sites with two alternative LDL apheresis systems being already in routine clinical use. In prospective cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In a recent study comparing LS-DL100 adsorbers and the DALI system, the ability to reduce LDL-C was rather similar with both methods [6]. This is in accordance with another comparison [7].…”
Section: Effects Of Ldl Apheresis Methods On Lipidssupporting
confidence: 75%
See 1 more Smart Citation
“…In a recent study comparing LS-DL100 adsorbers and the DALI system, the ability to reduce LDL-C was rather similar with both methods [6]. This is in accordance with another comparison [7].…”
Section: Effects Of Ldl Apheresis Methods On Lipidssupporting
confidence: 75%
“…In another study the LS DL-100 and the DALI systems were compared in six patients (two treatments with each method) [6]. The effect on fibrinogen concentrations was different between these methods (FIGURE 8A).…”
Section: Effects Of Ldl Apheresis Methods On Coagulation Factorsmentioning
confidence: 99%
“…Their substantial reduction by different apheresis techniques may constitute an additional beneficial mechanism of apheresis beyond lowering apoBcontaining lipoproteins [11]. The two lipoprotein apheresis techniques LF and DSA are safe and efficient therapeutic options for lipoprotein elimination and prevention of cardiovascular disease [12]. In contrast to LF, which implicates separation of plasma from blood cells, DSA does not require prior plasma separation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…HDL-cholesterol is typically reduced from 10% to 20% [1] as we also noted. There are few studies comparing columns head-to-head, but Julius et al found a more pronounced decrease in LDL cholesterol in whole blood apheresis than in LDL plasma apheresis, however stating that both methods are clinically effective and that LDL reduction partly is a function of treated volume [32]. Poli and Busnach compared two different whole blood apheresis systems (direct adsorption with a polyacrylic acid column vs. adsorption with a modified dextran sulfate column) and found LDL reductions of 62% and 59%, respectively, in accordance with our findings [33].…”
Section: Lipid Parametersmentioning
confidence: 99%